Research on Transient Torsional Vibration Test of Harmonic Reducer. Issue 1 (1st November 2022) - Xu, Tianhao; Tan, Jing; Huang, Dishan; Tong, Tong; Gu, Jingjun
Abstract: The torsional vibration of harmonic reducer is related to the positioning accuracy and Trajectory Accuracy of industrial robots. Based on this, this paper studies and experiments the impact response of harmonic reducer. By establishing the torsional vibration model with periodic variable stiffness of harmonic reducer, the unit impulse response and characteristics are analyzed; The time-varying torsional stiffness of the harmonic reducer is verified by setting up an experimental platform for the harmonic reducer, and the transient torsional vibration characteristics of the harmonic reducer are obtained The research will provide basic data for the optimal application of harmonic reducer.